A written treatment and summary of "The Happiness Test". - Tan, Faraliza Fadzli. (2009)
This written treatment and summary presents the rationale behind The Happiness Test and illustrates the scriptwriting process from conception to finish. It provides a description of our story and the characters created plus a detailed analysis of the themes and comedy genre of our screenplay. It also summarises our script's production feasibility, insights learnt and the obstacles overcome.